CONSTRUCTION OF SEXUAL DEVIATION PREVENTION FROM THE PERSPECTIVE OF ISLAMIC EDUCATION - Ela Hodijah N (STAI Sebelas April Sumedang, 2023)
Propaganda of sexual deviance is the current global agenda. Sexual deviance occurs in a real, significant and growing manner to the point where social society is encouraged to unconsciously construct sexual deviance as something normal. They always take action to demand that it be normalized in legislation that is recognized and protected by law. Instigators and instigators of the sexual deviance movement aggressively promote their activities to gain this recognition. They argue that their community is part of the existing social order and must be recognized. They urge society to accept their minority community, whether as commercial sex workers, film workers, dramas with adultery nuances, there are even many dramas in the genre Boys Love (BL) or Girls Love (GL), namely dramas about homosexuals, Gays or lesbians. They refine the term for adulterers, but in essence, adultery, whatever its form or name, is a forbidden act. Allah Subhanahu wa Ta`ala. The real problems in student relationships at STAI Sebelas April Sumedang include friendships in class, the interactions of students who are actively involved in various student organizations, the style of dating seems increasingly free. Minister of Education and Culture Regulation No. 20 of 2021 concerning the protection and prevention of sexual violence in higher education is a justification for the academic community to express sexual desires freely. A free lifestyle without knowing the boundaries of mahram has become commonplace in society, and increasingly lax supervision requires taking preventive breakthroughs. The research method uses qualitative data. The researcher's primary data source examines literacy, especially the Koran, Surah An-Nur verse 30, from various points of view starting from interpretation and meaning, implementation and collaboration. Other data was obtained from the results of free structured interviews, then described, verified, and then drawn into a new assumption as a novelty regarding the construction of religion in preventing sexual deviation among STAI Sebelas April Sumedang students. Research Results, meaning of QS. An-Nur Verse 30, the level of faith of a servant is to lower his gaze on things that are forbidden as an effort to maintain his honor and religion because it is the driving force behind disobedience and adultery. Implementation of prevention of sexual deviation in higher education, including; Behaving in accordance with Islamic Sharia, interacting intelligently, civilly and with ethical patience, creating a religious environment and involvement of the campus community, and being responsible in using internet information and other technology. Construction of text study Q.S. An-Nur:30 offers three breakthroughs; Conversations Strengthen Understanding, Strengthen Collaboration, and Strengthen Public Policy